2015
DOI: 10.1586/14779072.2015.1039991
|View full text |Cite
|
Sign up to set email alerts
|

Current and future trends in multimodality imaging of coronary artery disease

Abstract: Nowadays, there is a wide array of imaging studies available for the evaluation of coronary artery disease, each with its particular indications and strengths. Cardiac single photon emission tomography is mostly used to evaluate myocardial perfusion, having experienced recent marked improvements in image acquisition. Cardiac PET has its main utility in perfusion imaging, atherosclerosis and endothelial function evaluation, and viability assessment. Cardiovascular computed tomography has long been used as a ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…Navare et al [21] found that exercise stress MPI and pharmacological stress MPI have comparable ability to diagnose and risk stratify patients when used accordingly. Stress MPI provides excellent diagnostic accuracy for CAD with sensitivity and specificity of 87–89% and 70–79%, respectively [22]. The average sensitivity and specificity for the detection of CAD is 88% and 69%, and for exercise MPI and for adenosine MPI, 90% and 81%, respectively.…”
Section: Non-invasive Imaging Modalitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Navare et al [21] found that exercise stress MPI and pharmacological stress MPI have comparable ability to diagnose and risk stratify patients when used accordingly. Stress MPI provides excellent diagnostic accuracy for CAD with sensitivity and specificity of 87–89% and 70–79%, respectively [22]. The average sensitivity and specificity for the detection of CAD is 88% and 69%, and for exercise MPI and for adenosine MPI, 90% and 81%, respectively.…”
Section: Non-invasive Imaging Modalitiesmentioning
confidence: 99%
“…In addition, artifacts secondary to breast tissue, respiratory motion or sub-diaphragmatic attenuation are known to occur. Techniques such as attenuation correction has allowed for improvements in characterization of perfusion defections by reducing artifacts created by surrounding tissue particularly in women and obese patients [22,30,31]. …”
Section: Non-invasive Imaging Modalitiesmentioning
confidence: 99%
See 3 more Smart Citations